Bacteria biohybrid oral vaccines for colorectal cancer treatment reduce tumor growth and increase immune infiltration. Issue 39 (15th September 2021) - Naciute, Milda; Kiwitt, Tamara; Kemp, Roslyn A.; Hook, Sarah
Graphical abstract: Abstract: Bacteria biohybrid-based vaccine delivery systems, which integrate a vaccine carrier with live non-pathogenic bacteria, are hypothesized to have improved immunostimulating potential. The aim of this study was to develop oral bacteria biohybrid-based vaccines to treat a mouse model of colorectal cancer. E. coli were combined with tumor antigen- and adjuvant-containing emulsions or liposomes. Emulsion and liposome biohybrid vaccines demonstrated in vitro and in vivo therapeutic potential. Bacteria biohybrid vaccines significantly increased the expression of CD40 +, CD80 + and CD86 + on murine bone marrow-derived dendritic cells. Mice vaccinated with emulsion biohybrid vaccines had an increased CD8 + T cell infiltration into tumors and developed three-fold smaller tumors compared to the mice that received emulsion vaccine without E. coli .